DINAMIKA LEMBAGA SOSIAL DALAM KEHIDUPAN MASYARAKAT: PENDIDIKAN, POLITIK, EKONOMI, AGAMA, DAN HUKUM - Huda, Khoirul; Muzayyana, Lyra; Khan Siregar, Ali Aman (Studia Sosia Religia, 2026)
Social institutions constitute fundamental elements of social life that function to regulate patterns of interaction, fulfill basic social needs, and maintain social order. This article aims to analyze the roles and functions of educational, political, economic, religious, and legal institutions from sociological and Islamic perspectives. This study employs a qualitative approach using library research and descriptive-analytical methods by examining relevant sociological and Islamic studies literature. The findings indicate that from a sociological perspective, social institutions function as structural mechanisms that maintain social stability and integration. Meanwhile, from an Islamic perspective, these institutions are understood as instruments for realizing maslahah (public welfare), justice, and moral values. The integration of sociological analysis and Islamic values provides a comprehensive understanding that social institutions operate not only structurally but also normatively and ethically in shaping a civilized and just social order. This study is expected to contribute academically to the development of sociological and Islamic studies and to serve as a reference for strengthening social institutions amid contemporary societal dynamics.